Neutron-induced 37Ar recoil ejection in Ca-rich minerals and implications for 40Ar/39Ar dating - Jourdan, Fred; Renne, P. (Geological Society Publishing House, 2013)
The 40Ar/39Ar dating technique requires the transformation of 39K into 39Ar by neutron activation. Neutron activation has undesirable secondary effects such as interfering isotope production, and recoil of 39Ar and 37Ar atoms from their (dominant) targets of K and Ca. In most cases, the grains analysed are large enough (>50 μm) such that the amount of target atoms ejected from the grains is small and has a negligible effect on the ages obtained. However, increasing needs to date fine-grained rocks requires constraining, and in some cases correcting for, the effect of nuclear recoil. Previous quantitative studies of recoil loss focus mostly on 39Ar. However, 37Ar loss can affect the ages of Ca-rich minerals via interference corrections on 36Ar (and, to a lesser extent, 39Ar), yielding lower 40Ar*/39ArK and, thus, an age spuriously too young. New results focused on 37Ar recoil by measuring the apparent age of multi-grain populations of Ca-rich minerals including Fish Canyon plagioclase (FCp) and Hb3gr hornblende, with discrete sizes ranging from 210 to <5 µm.We use previous result on sanidine grains to correct for the 39Ar recoil loss. For the finest fractions, FCp and Hb3gr apparent ages are younger than the 39Ar recoil-corrected ages expected for these minerals, with a maximum deviation of −40% (FCp) and −21% (Hb3gr) reached for grains below 5 μm. We calculate 37Ar-depletion values ranging from approximately 30 to 91% and from approximately 28 to 98% for plagioclase and hornblende, respectively. This results in x0 values (mean thickness of the partial depletion layer) of 3.3±0.4 μm (2σ; FCp) and 3.6±1.4 μm (Hb3gr), significantly higher than suggested by current models. The reason for the substantial 37Ar loss is not well understood, but might be related to the radiation damage caused to the mineral during irradiation. x0 (39Ar) and x0 (37Ar) values obtained in this study, along with crystal dimensions, can be used for correcting 40Ar/39Ar ages from 39Ar and 37Ar recoil loss. We also discuss the relevance of our results to vacuum-encapsulation studies and isotopic redistribution in fine-grained minerals.